Uncovering the uncommon: a primary pyomyositis of vastus muscle by Streptococcus pyogenes in an immunocompetent child - Faisal, Ummu Salamah; Meor Jamaludin, Wan Husna Barakah; Abdul Tahrim, Muhammad Zaki; Ramli, Ramliza; Zainulabid, Ummu Afeera (2023)
Pyomyositis is a condition where a primary muscle abscess forms within the striated muscle. "Tropical pyomyositis" refers to the disease's prevalence in tropical countries with high temperatures and humidity. Staphylococcus aureus is the most common organism involved, followed by other organisms such as Group A Streptococcus, Streptococcus Groups B, C, and G, pneumococcus, Neisseria sp., Haemophilus sp., Aeromonas sp., Pseudomonas sp., Klebsiella sp., and Escherichia coli. This case report describes a rare case of primary pyomyositis of the vastus muscle caused by Streptococcus pyogenes in an immunocompetent 12-year-old boy. The patient presented with severe right thigh pain and fever following a fall during a football game. The initial diagnosis was viral myositis. However, subsequent imaging revealed an avulsion fracture of the right lesser trochanter apophysis complicated with an infected hematoma. The patient was treated with antibiotics. He underwent ultrasound-guided drainage of the hematoma. Bacterial culture and sensitivity testing identified Streptococcus pyogenes. The patient recovered fully after a two-week hospital stay and continued oral antibiotics for another four weeks. This case highlights a rare presentation of pyomyositis of the vastus medialis muscle, which can mimic other conditions. A proper diagnosis can be established by aspiration of pus from the muscle or muscle biopsy with culture and tissue staining in cases of absent macroabscesses. Tropical pyomyositis should be considered in the differential diagnosis of any patient presenting with muscle pain, fever, and/or leucocytosis.